Predicting future volunteering intentions through a self-determination theory perspective - Wu, Y.; Li, C.; Khoo, S. (Springer Verlag, 2015)
Using self-determination theory (SDT; Deci and Ryan 1985), we conducted a cross-sectional survey to test the relationship among competence, intrinsic motivation, job satisfaction, and intention to continue volunteering. A total of 180 Special Olympics volunteers from China participated in this study. The results showed that competence positively predicted intrinsic motivation and job satisfaction. Intrinsic motivation was a partial mediator for the relationship between competence and job satisfaction. Job satisfaction positively influenced intention and it acted as a full mediator in the relationship between intrinsic motivation and intention. It was concluded that SDT is a useful theoretical framework in understanding intention to continue volunteering. Theoretical and practical implications are provided.